Critical Thinking Dispositions as a Predictor for High School Students’ Environmental Attitudes - Ali Orhan (Journal of Education in Science, Environment and Health)
This non-experimental quantitative study aimed to determine if high school students’ critical thinking (CT) dispositions and environmental attitudes differ by gender, father, and mother’s educational background and their CT dispositions are significant predictors of environmental attitudes. UF/EMI Critical Thinking Disposition Instrument and Environmental Attitude Scale were used to collect data in this study carried out with 139 high school students. It was found out that students’ CT dispositions did not differ by gender, father, and mother’s educational background. Also, while students’ environmental attitudes differed by gender in favor of females, they did not differ by mother and father’s educational background. Besides, engagement, maturity, and innovativeness were significant predictors of the students’ environmental attitudes. A positive relationship was found between students’ CT dispositions and environmental attitude scores and engagement, maturity, and innovativeness together explained 31% of the total variance on their environmental attitudes.